PENYULUHAN PROGRAM PENGEMBANGAN KEWIRAUSAHAAN PEMUDA DESA ARANG-ARANG - Adriani, Evi; Fahmi, Ali; Basri, Hasan; Azizah, Azizah; Johar, Leily Wustha (Yayasan Cita Cendikiawan Al Kharizmi, 2025)
The purpose of this community service activity is that the young generation who are members of the Karang Taruna of Arang-Arang Village, Kumpeh Ulu District, Muaro Jambi Regency generally lack the knowledge and ability to choose business opportunities that they will do. Based on this fact, the target of this service is members of the Karang Taruna who do not yet have a Micro Small Business. The method of the activity is Entrepreneurship Socialization so that it can increase understanding of the business world and open a business. The delivery of the extension material is used with several relevant methods, including: lecture method, question and answer, and discussion. After the event is finished, the participants are given a questionnaire to measure the extent to which the objectives of this extension have been achieved. Evaluation technique: carried out through question and answer methods and questionnaires to measure the participants' abilities in the extension material. The results of this activity are implementing Community Service as a practice of science, technology and art to accelerate the rate of growth of village development. It is concluded that with this forum, Youth can cooperate with Legal Entities so that the business that will be carried out can involve third parties.